2017
DOI: 10.1042/ns20160020
|View full text |Cite
|
Sign up to set email alerts
|

AMPK: keeping the (power)house in order?

Abstract: Metabolically energetic organs, such as the brain, require a reliable source of ATP, the majority of which is provided by oxidative phosphorylation in the mitochondrial matrix. Maintaining mitochondrial integrity is therefore of paramount importance in highly specialized cells such as neurons. Beyond acting as cellular 'power stations' and initiators of apoptosis, neuronal mitochondria are highly mobile, transported to pre-and post-synaptic sites for rapid, localized ATP production, serve to buffer physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…When activated, AMPK phosphorylates mitochondrial fission factor (MFF), recruiting Drp1 from the cytosol to the mitochondrial outer membrane, thus promoting the constriction and fission of mitochondria, which may serve as one way for engulfment of mitochondria by autophagosome or mitophagy because of mitochondrial fragments that indicate extensive damage 56 . In our study, we found that CO‐EtOAc led to increased protein expression of DRP1 in mitochondrial and AMPK activation was essential for their full action in the promotion of mitochondrial fission, which has been reported to be a consequence of ATP depletion 57 …”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…When activated, AMPK phosphorylates mitochondrial fission factor (MFF), recruiting Drp1 from the cytosol to the mitochondrial outer membrane, thus promoting the constriction and fission of mitochondria, which may serve as one way for engulfment of mitochondria by autophagosome or mitophagy because of mitochondrial fragments that indicate extensive damage 56 . In our study, we found that CO‐EtOAc led to increased protein expression of DRP1 in mitochondrial and AMPK activation was essential for their full action in the promotion of mitochondrial fission, which has been reported to be a consequence of ATP depletion 57 …”
Section: Discussionsupporting
confidence: 51%
“…56 In our study, we found that CO-EtOAc led to increased protein expression of DRP1 in mitochondrial and AMPK activation was essential for their full action in the promotion of mitochondrial fission, which has been reported to be a consequence of ATP depletion. 57 In conclusion, our studies demonstrated the beneficial effects of a natural product, CO-EtOAc, as a potent activator of AMPK, which regulates glucose homeostasis both in vitro and in vivo. CO-EtOAc caused inhibition of mitochondrial oxygen consumption, thus leading to the activation of AMPK and subsequent beneficial metabolic outcomes, including enhanced glucose uptake and glycogen content in skeletal muscle cells (Figure 9).…”
Section: F I G U R Ementioning
confidence: 57%
“…As modulators of intracellular energy status, both AMPK and PGC1α are extremely active after brain injury [ 47 ]. Gao et al [ 48 ] found that AMPK/PGC1α pathway activation protected mitochondrial biosynthesis and function in cerebral ischemic stroke, while inhibition of this pathway can aggravate cerebral ischemia/reperfusion injury [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress-associated AMPK activation occurs from a direct mechanism involving depleted adenosine triphosphate (ATP) levels that raise cytoplasmic adenosine mono/diphosphate (AMP/ADP) levels [ 109 , 110 ] ( Figure 4 ). AMPK is also activated by three upstream regulators in response to different stimuli: (1) liver kinase B1 (LKB1), which responds to cellular energy levels; (2) Ca 2+ /calmodulin-dependent kinase kinase β (CaMKKß) activation by increased cytoplasmic calcium (Ca 2+ ) from ER stress; and (3) transforming growth factor-β (TGF-β)-activated kinase 1 (TAK1) [ 106 , 107 , 111 , 112 ] [ 113 , 114 ] ( Figure 4 ).…”
Section: Autophagymentioning
confidence: 99%
“…Once activated, AMPK upregulates autophagy via from 3 major pathways: (1) phosphorylation and deactivation of Raptor (a protein within the mTORC1); (2) activation of TSC2, causing RHEB inhibition and subsequent mTORC1 inhibition; and (3) ULK1 phosphorylation at Ser317 and Ser777 sites [ 53 , 54 , 94 , 115 ] ( Figure 4 ). It should also be noted that the activation of TSC2 can directly oppose the PI3K pathway-induced autophagic suppression [ 106 , 107 , 111 ]. Collectively, AMPK is a vital autophagic activator which has a complex, yet well understood, mechanism of activating autophagy.…”
Section: Autophagymentioning
confidence: 99%